ERRATIC ELECTRICITY SUPPLY, SMALL AND MEDIUM ENTERPRISES IN AKWA-IBOM STATE: A CASE STUDY OF UYO LOCAL GOVERNMENT AREA - Nathan Udoinyang (International Journal of Integrated Science and Technology, 2024)
Small and medium-sized businesses in Uyo Local Government Area, Akwa Ibom State, Nigeria, had their power usage and productivity examined in this study. The businesses were affected by an unstable energy supply. The research used both primary and secondary sources to compile its population, which is all small and medium-sized enterprises (SMEs) in the Uyo senatorial district as registered by the Akwa Ibom State directorate of SMEs in 2021. A sample size of 400 was achieved by using the equations developed by Taro Yamane. With the use of a purposive sampling methodology, 400 questionnaires were circulated and, ultimately, 340 were collected. Using a mean criteria of 3.0, the questionnaire was evaluated using a 5-point Likert scale. According to the research, SMEs suffer when there is an unpredictable supply of energy, which may lead to a drop in profit, a drop in sales, more money spent on finding a new power source, problems expanding, and more. In conclusion, SMEs in Uyo LGA, Akwa Ibom State, would benefit economically from a steady and dependable power supply, which will raise employment, sales, revenue, profitability, and productivity while decreasing expenditure and reliance on alternative energy sources. Therefore, the study suggests that the council boss and the state government work together to extend the duration of the area's electricity supply, prioritize stable electricity supply, and funnel taxes collected from SMEs into amenities that will benefit SMEs across Akwa Ibom State and Uyo LGA.